The Making and Unmaking of Opportunity: Educational Mobility in 20th Century-Denmark - Kristian B. Karlson; Rasmus Landerso (Institute of Labor Economics (IZA), 2021)
We study intergenerational educational mobility in Denmark over the 20th century during which the comprehensive Danish welfare state was rolled out. While mobility initially was low, schooling reforms benefiting children from disadvantaged backgrounds led to dramatic increases in mobility for cohorts born between 1940 and 1960. However, the college expansion affecting cohorts born from 1970 onward has mainly benefited children from affluent backgrounds, resulting in rapidly declining mobility. Comparisons to educational mobility trends in the U.S. reveal that the two countries converge in mobility levels for the most recent cohorts despite the dramatically different welfare policies in place.
Keywords: H0; I0; J0; 330; educational mobility; inequality; schooling reforms; skills